Angiopoietin-2 correlates with pulmonary embolism severity, right ventricular dysfunction, and intensive care unit admission. (October 2021) - Newman, Joshua; Brailovsky, Yevgeniy; Allen, Sorcha; Bontekoe, Emily; Masic, Dalila; Walenga, Jeanine; Fareed, Jawed; Darki, Amir
Risk stratification of acute pulmonary embolism (PE) is important to identify patients at risk for hemodynamic collapse who would benefit from more aggressive therapies. Angiopoietin-2 (Ang-2) is a signaling molecule involved in angiogenesis and is upregulated in response to tissue hypoxia. We aimed to assess the association of Ang-2 with (1) PE severity, (2) echocardiographic and invasive hemodynamic markers of right ventricular (RV) dysfunction, and (3) need for intensive treatment. Patients presenting to our institution with acute PE were included in a prospective database and blood samples were collected and stored for later analysis. A total of 65 patients were included in the study. Ang-2 correlated with PE risk stratification and echocardiographic and invasive hemodynamic markers of RV dysfunction and pulmonary hypertension. An Ang-2 level of > 4101 pg/mL had an odds ratio of 7.4 (95% CI: 1.53–12.5, p < 0.01) for intensive care unit (ICU) admission. In conclusion, Ang-2 correlates with PE severity, RV dysfunction, and need for ICU admission. Ang-2 holds promise as a novel marker that can aid in risk stratification for this patient population.